The response clamp: functional characterization of neural systems using closed-loop control - Wallach, Avner (Frontiers in Neural Circuits, 2013)
The voltage clamp method, pioneered by Hodgkin, Huxley and Katz, laid the foundations to neurophysiological research. Its core rationale is the use of closed-loop control as a tool for system characterization. A recently introduced method, the response clamp, extends the voltage clamp rationale to the functional, phenomenological level. The method consists of on-line estimation of a response variable of interest (e.g. the probability of response or its latency) and a simple feedback control mechanism designed to tightly converge this variable towards a desired trajectory. In the present contribution I offer a perspective on this novel method and its applications in the broader context of system identification and characterization. First, I demonstrate how internal state variables are exposed using the method, and how the use of several controllers may allow for a detailed, multi-variable characterization of the system. Second, I discuss three different categories of applications of the method: (i) exploration of intrinsically generated dynamics, (ii) exploration of extrinsically generated dynamics and (iii) generation of input-output trajectories. The relation of these categories to similar uses in the voltage clamp and other techniques is also discussed. Finally, I discuss the method’s limitations, as well as its possible synthesis with existing complementary approaches.